The obesity‐related Adipokinetic hormone controls feeding and expression of neuropeptide regulators of Drosophila metabolism. Issue 3 (21st June 2016) - Gáliková, Martina; Klepsatel, Peter; Xu, Yanjun; Kühnlein, Ronald P.
Abstract : Homeostasis of circulating and storage energy reserves in mammals is dependent on the antagonistically acting insulin and glucagon signaling. In the model organism Drosophila melanogaster, this function is executed by the insulin‐like peptides and the glucagon‐like Adipokinetic hormone (AKH). Loss of Drosophila AKH results in the adulthood‐specific onset of obesity coupled with hypoglycemia. However, apart from the role of AKH in the lipid mobilization, the physiological and endocrine underpinnings of the AKH deficiency‐triggered obesity are unknown. Here, we investigate the role of AKH in feeding and metabolic rate control, and address the interactions of this hormone with other endocrine regulators of fly metabolism. Via in vivo gain‐ and loss‐of‐function analyses, we show that despite its anti‐obesity effects, AKH is an orexigenic peptide. Moreover, AKH also affects expression of orexigenic factors CCHamide‐2 and neuropeptide F . In addition, AKH regulates metabolic genes like Corazonin, Limostatin, and Insulin‐like peptides ( Ilps ) 2, 3, 5, and 6 . Altogether, our work shows that the Drosophila AKH is a central regulator of energy homeostasis; next to its well‐known role in the control of energy expenditure, this hormone controls also food intake, and expression of other endocrine regulators of fly metabolism. Practical applications: Basic research of the neuroendocrine regulation of metabolism in the fruit fly D. melanogaster has potential applications in both human medicine and insect pest control. The evolutionary conservation of the key metabolic pathways, together with the unprecedented choice of transgenic tools turned the fruit fly into a useful model to study human diseases, including obesity and diabetes. Based on the evolutionary conservation of AKH and glucagon functions, our investigations might provide useful hints regarding the physiological actions, and endocrine interactions of human glucagon, too. In addition, insect neuropeptides are emerging as important targets for the parasite and pest control; understanding of their regulatory networks has thus potential implications also in the development of novel insecticides. Adipokinetic hormone (AKH) is an insect analog of the human hormone glucagon. Our investigations of the roles of this hormone in the model organism Drosophila melanogaster have shown that this anti‐obesity factor is a central regulator of fly metabolism, and controls crucial processes such as feeding, metabolic rate, storage of energy reserves, and expression of regulatory genes from the neuropeptide hormone family, including the fly homologs of human insulin. Abstract : Adipokinetic hormone (AKH) is an insect analog of the human hormone glucagon. Our investigations of the roles of this hormone in the model organism Drosophila melanogaster have shown that this anti‐obesity factor is a central regulator of fly metabolism, and controls crucial processes such as feeding, metabolic rate, storage of energy reserves, and expression of regulatory genes from the neuropeptide hormone family, including the fly homologs of human insulin.